Older Adult Education in the Context of Psychological Theories of Ageing - Nataliya Chahrak (Vasyl Stefanyk Precarpathian National University, 2024)
In gerontology, the essence of ageing is traditionally equated with decline and degradation, it is considered a purposeful process of loss of the body's adaptive capacity. Psychologists, in particular representatives of behaviorism, deny this position, instead they consider ageing to be an integral part of the general process of human development. Theories of ageing have progressed from focusing on individuals' declines and losses in later phase of their life course to considering ageing as a continuous process of human development. Psychological theories of ageing are crucial to understanding older adults as learners ‒ their needs, abilities, motivation of learning and expectations from educational activity. They help us to develop comprehensive approaches to building an effective educational environment and improving the learning process of that age and social group aiming to adapt that environment to the needs of older adult learners. The article analyzes the main provisions of psychological theories of ageing, which substantiate the importance and even the necessity of involving older adults in educational activities, because firstly, mental activity contributes to the preservation and even development of a person's intellectual capabilities until old age; secondly, in older people (compared to young people), changes in the ability to learn are insignificant and relate rather to the sphere of perception, attention, motivation, and the physiological state of the body; and thirdly, older people have a growing need for a sense of security, which has a significant impact on their quality of life and is largely realized through communication and learning activities. Based on the main tenets of psychological theories of ageing, in our research we consider older adults as a resource and human capital. We believe that the approach to the problem of ageing and old age from the resource perspective, which is based on the ideas of theories of activity and lifelong personality development, allows us to justify the need for education of older adults and is the basis of educational gerontology.